Analisis Kinerja Berdasarkan Balanced Scorecard di RSU Mayjen H A Thalib Kabupaten Kerinci Tahun 2012-2016 - Rio Baviga; Mukhzarudfa Mukhzarudfa; Zamzami Zamzami (Magister Ilmu Akuntansi Universitas Jambi, 2018)
Performance is the success of a personnel, team, or organizational unit in realizing a predetermined strategic goal with the expected behavior. Then required performance measurement using Balanced Scorecard approach in RSU Mayjen H A Thalib of Kerinci regency, in order to achieve the vision and strategy of the hospital. This research is done by using chi-square test result that there is influence between Growth and Learning and Internal Business Processes with value 0,083, the influence between Internal Business Processes and Customer Satisfaction with value 0,083, and the influence of Customer Satisfaction to Financial with value 0,233. The results of the performance measurement can be illustrated that the hospital is categorized as